Tax-benefit responses in Uruguay during the COVID-19 pandemic - Verónica Amarante; Federico Scalese (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
We analyse the social protection policy response to COVID-19 and its impact on household incomes in Uruguay during 2020 and 2021, based on static microsimulation methods. From the onset of the crisis, the Uruguayan government implemented adjustments to existing social protection policies as well as a new transfer and an emergency tax. The configuration of precrisis social protection facilitated the setting-up of rapid support for the vulnerable and for formal workers. The responses adopted by the Uruguayan government were an increase in the amount of existing cash transfers, the introduction of a new cash transfer programme to reach informal workers, and simplification of the requirements for unemployment insurance benefit. On the tax side, a temporary income tax (COVID-19 Emergency Tax) for public workers (excluding health workers) and pensioners receiving an income above a certain threshold was implemented during two months in 2020 and two months in 2021. Our results indicate that the modifications in the social protection system introduced in the face of COVID-19 allowed a reduction in the incidence of poverty by 1.3 and 1.6 percentage points in 2020 and 2021,respectively. The effects were bigger among households with children: if no modifications had been undertaken in social protection as a response to COVID-19, poverty would have been 1.8 or 2.4 percentage points higher for these households in 2020 and 2021, respectively. The most important instruments were unemployment insurance in 2020 and the conditional cash transfer directed at households with children in 2021. Taken together, thesemodifications to the social protection system prevented the Gini Index from increasing by 0.6/0.7 additional percentage points.
Keywords: D31; E24; H24; 330; COVID-19; taxes; benefits; poverty; inequality; Uruguay